SANATAN VALUES AND HUMAN LIFE: AN ANALYTICAL STUDY - Soni, Dr. Priya Soni Khare; Jitendra Kumar (International Journal of Research -GRANTHAALAYAH, 2025)
Sanatan Values and Human Life is a deep and thoughtful subject, which understands the enduring principles of Indian culture and philosophy and analyzes their impact on human life. Sanatan values are those universal principles which guide human life towards progress from spiritual, mental and social perspectives, irrespective of time, place and circumstances. These values inspire us to follow ethics and ideals in every aspect of our life, thereby establishing peace, harmony and prosperity in the society. This article highlights the importance of Sanatan values and their relevance in the current context. It explains that these values are not only important from a religious and spiritual point of view, but are also helpful in creating harmony and self-knowledge in society. Sanatan values such as truth, non-violence, Dharma, charity, and self-knowledge are as important in our lives today as they were thousands of years ago. Additionally, the article presents various aspects of Sanatan values, their impact, results, and suggestions, which show that following these values leads to the progress of both the individual and the society. It also explains through examples how by inculcating these values in life, a person can make his life balanced and purposeful.